Review of Nonmelanoma Skin Cancer in African Americans, Hispanics, and Asians. Issue 7 (July 2018) - Higgins, Shauna; Nazemi, Azadeh; Chow, Maggie; Wysong, Ashley
Abstract : BACKGROUND: Skin cancer has traditionally been studied in Caucasian skin. Although it does occur with increased relative frequency in Caucasians, patients with skin of color suffer from elevated morbidity and mortality when diagnosed with skin cancer. OBJECTIVE: To detail the unique demographic and clinical features of nonmelanoma skin cancer (NMSC) in patients with skin of color, including Hispanic, African American, and Asian patients. MATERIALS AND METHODS: A complete PubMed search was conducted spanning dates from 1947 to June 2017 yielding a total of 185 manuscripts, from which 45 were included in this review. RESULTS: Relative to Caucasians, NMSC, comprised squamous cell carcinoma and basal cell carcinoma, has unique demographic and clinical features in African Americans, Hispanics, and Asians. CONCLUSION: Familiarization with these unique presentations of skin cancer in skin of color is imperative to accurate identification and treatment of cutaneous malignancies in these populations and ultimately to improved disease-related outcomes.